PROGRAM LITERASI INFORMASI BERTEMA SEJARAH DI SD NASIMA - Ario Adi Prakoso (Fakultas Ilmu Komunikasi Universitas Islam Nusantara, 2021)
Currently, many children understand technology, so information search is done through the internet instead of libraries, and technology also makes children more aware of the history of other countries than the history of Indonesia. The purpose of this study is to find out information literacy programs with historical themes at Nasima Elementary School. This study used the descriptive qualitative method. The research subjects were school students and librarians of SD Nasima. The results of the big 6 analysis, namely Task Definition, the librarian gave the task to students to find out about history. At the stage of Information Seeking Strategies. Students determine what sources will be used such as books, magazines, audio, video, and others. In the Location and Access stage, students visit the library. In the Use of Information stage, students are asked to read, listen and watch. At the Synthesis stage, students combine information from various sources and are asked to present the results of the information obtained. At the Evaluation stage, students evaluate what has been done. The most effective activity for students to receive the information presented is by watching videos.Keywords: school library; information literacy; information architecture; the big 6ABSTRAKSaat ini banyak anak-anak paham teknologi, sehingga pencarian informasi dilakukan melalui internet bukan perpustakaan, dan teknologi juga membuat anak-anak lebih paham sejarah negara lain daripada sejarah Indonesia. Tujuan dari penelitian ini adalah untuk mengetahui program literasi informasi bertema sejarah di SD Nasima. Penelitian ini menggunakan metode deskriptif kualitatif. Subjek penelitian adalah siswa sekolah dan pustakawan SD Nasima. Hasil analisis the big 6, yaitu task definition pustakawan memberi tugas kepada siswa untuk mencari tahu tentang sejarah. Pada tahap information seeking strategies. siswa menentukan sumber apa yang akan dipakai seperti buku, majalah, audio, video dan lain-lain. Pada tahap location and access siswa mengunjungi perpustakaan. pada tahap use of information siswa diminta membaca, mendengarkan dan menonton. pada tahap synthesis siswa menggabungkan informasi dari berbagai sumber, dan diminta untuk mempresentasikan dari hasil informasi yang didapatkan. Pada tahap evaluation, siswa mengevaluasi dari apa yang sudah dilakukan. Adapun kegiatan yang paling efektif dalam siswa menerima informasi yang disampaikan adalah dengan menonton video.